Agile supply partnerships : the paradox of high-involvement and short-term supply relationships in the Macerata-Fermo footwear district - Cerruti, Corrado (Cranfield University, 2013)
Despite a general consensus concerning the relevance of supply partnerships to agility, the literature reveals disagreements and contradictions regarding their characteristics and, in particular, their duration. This is, whether partnerships in an agile strategy should be long-term (strategic partnerships) or short-term (agile partnerships). The research joins this debate by investigating the types and characteristics of supply partnerships to achieve agility. The underlying premise of the work is that the type of supply partnership is contingent on the degree of turbulence an agile strategy is designed to face. The research was carried out in the fashion industry, given the relevance of agility in this industry. Specifically, the research focused the supply partnerships developed by the footwear companies in the Macerata-Fermo district, the largest footwear district in Italy. The focus on district companies allow the comparison of several companies sharing a very similar business context, allowing a better control of external variables and increasing the internal validity of the study. The field research consisted of a preliminary survey on agility drivers and agile capabilities in the Macerata-Fermo footwear district, followed by an in-depth investigation on supply partnerships using multiple embedded cases studies. Overall six medium-large footwear companies have been analysed in their supply relationships with respect to five key supply categories. For each supply category, the buyer view of the focal firms has been complemented with a view from the supplier side. In total the fieldwork is built upon 30 interviews with 22 informants from 18 companies for a total of more than 23 hours of interviews. In all cases, except two, the key informant was owner, CEO or general manager of the company, eventually supported by another company manager. In two cases, the interviews data have been strengthened by a longitudinal analysis of purchase orders over eight years. The fieldwork highlights that agility drivers and agile capabilities impact on the footwear companies’ decision of developing agile supply partnerships. Specifically footwear companies that are under the pressure of high-turbulence agility drivers (here represented by a high collection renewal rate) and that have developed strong agile capabilities (here represented by a local supply network and a purchase orders postponement) choose agile supply partnerships with respect to supply categories that are sensitive to the fashion trends and therefore difficult to be sourced in a stable way – season after season – from the same suppliers. The main contribution to theory is related to the characteristics of supply partnerships in an agile strategy and specifically to the apparent paradox of “high-involvement & short- term” relationships (i.e. agile supply partnerships). In spite of the presence of time compression diseconomies in building up partnership and of the loss of relational (non- redeployable) benefits in closing down partnerships, scenarios of high-turbulence can give companies an incentive to look for short-term partnerships. Such finding can support a wider claim that different levels of turbulence call for different agility strategies requiring different capabilities and practices. The main contribution to practice is related to the way agile partnerships are selected, started and ended. Given that many industries are facing an increase in market turbulence, it appears that many companies – even outside the fashion industry – might have to learn how to balance high-involvement supply relationships with respect to a shorter time horizon.
Keywords: agility; relationships; buyer-supplier; long-term; systematic literature review